DETERMINASI PEMBANGUNAN BERKELANJUTAN DI INDONESIA DENGAN MENGGUNAKAN MODEL QUADRUPLE HELIX - Lutfi, Muhammad Yudhi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This research has two objectives, namely (1) measuring the SGDs index and (2) analyzing the role of development actors using the Quadruple Helix model which is a collaborative cooperation concept with a network that connects academics, government, industry and society, each of which will carry out appropriate development functions. based on common interests. The SDGs index is a composite index of the HDI which is a combination of economic and social pillars, IKLH to measure the environmental pillar and IDI is an indicator for the pillars of governance and law in Indonesia. The government's role in the SDGs is in accordance with its function as an allocator, distributor and stabilizer as measured by the variabels Ratio of Regional Government Expenditure to GRDP, Ratio of Regional Tax to GRDP, Inflation level and Regional Financial Effectiveness, while the role of the private sector is measured by the amount of Private Investment, Banking Credit and Per Capita Consumption Expenditure. The role of universities in achieving the SDGs is shown by the large Gross Participation Rate (APK) of universities and community indicators in society measured by the performance of micro and small businesses. The estimation method used is panel data analysis covering 33 provinces in 2016-2020, and the best model chosen is random effect. The dependent variable is the Sustainable Development Index, and the dependent variables include; Regional Government Expenditures, Tax Ratio is the ratio of regional taxes to Gross Regional Domestic Product (GRDP), Inflation, The level of effectiveness of regional, The amount of bank credit per province, Private Investment, Performance of Micro and Small enterprises, and Gross Participation Rate. The estimation results show that regional financial indicators significantly influence the SDGs index, while indicators of the role of industry show that the banking sector has not been significant in financing the implementation of the SDGs, while the performance of Micro and Small Enterprises has a significant positive influence on the SDGs Index.